Decellularized Splenic Matrix as a Scaffold for Spleen Bioengineering - Zanardo, Tadeu Ériton Caliman; Amorim, Fernanda Gobbi; Taufner, Gabriel Henrique; Pereira, Rayssa Helena Arruda; Baiense, Ian Manhoni; Destefani, Afrânio Côgo; Iwai, Leo Kei; Maranhão, Raul Cavalcante; Nogueira, Breno Valentim (Frontiers in Bioengineering and Biotechnology, 2020)
The spleen is considered a non-essential organ. However, its importance is increasingly clear, given the serious disorders caused by its absence or dysfunction, e.g., greater susceptibility to infections, thromboembolism and cancer. Surgical techniques to preserve the spleen and maintain splenic function have become increasingly common. However, the morbidity and mortality associated with its absence and dysfunction are still high. We used the decellularization technique to obtain a viable splenic scaffold for recellularization in vitro and propose the idea of bioengineered spleen transplantation to the host. We observed the maintenance of important structural components such as white pulp, marginal zone and red pulp, in addition to the network of vascular ducts. The decellularized scaffold presents minimal residual DNA and SDS, which are essential to prevent immunogenic responses and transplantation failure. Also, the main components of the splenic matrix were preserved after decellularization, with retention of approximately 72% in the matrisomal protein content. The scaffold we developed was partially recellularized with stromal cells from the spleen of neonatal rats, demonstrating adhesion, proliferation and viability of cells. Therefore, the splenic scaffold is very promising for use in studies on spleen reconstruction and transplantation, with the aim of complete recovery of splenic function.